Optimization technique with sensitivity analysis on menu scheduling for boarding school student aged 13-18 using “Sufahani-Ismail Algorithm” - M. Sudin, Azila; Sufahani, Suliadi (2018)
Boarding school student aged 13-18 need to eat nutritious meals which contains proper calories, vitality and nutrients for appropriate development with a specific end goal to repair and upkeep the body tissues. Furthermore, it averts undesired diseases and contamination. Serving healthier food is a noteworthy stride towards accomplishing that goal. However, arranging a nutritious and balance menu manually is convoluted, wasteful and tedious. Therefore, the aim of this study is to develop a mathematical model with an optimization technique for menu scheduling that fulfill the whole supplement prerequisite for boarding school student, reduce processing time, minimize the budget and furthermore serve assortment type of food each day. It additionally gives the flexibility for the cook to choose any food to be considered in the beginning of the process and change any favored menu even after the ideal arrangement and optimal solution has been obtained. This is called sensitivity analysis. A recalculation procedure will be performed in light of the ideal arrangement and seven days menu was produced. The data was gathered from the Malaysian Ministry of Education and schools authorities. Menu arranging is a known optimization problem. Therefore Binary Programming alongside optimization technique and “Sufahani-Ismail Algorithm” were utilized to take care of this issue. In future, this model can be implemented to other menu problem, for example, for sports, endless disease patients, militaries, colleges, healing facilities and nursing homes.